2022
DOI: 10.1097/icb.0000000000001026
|View full text |Cite
|
Sign up to set email alerts
|

Dark Without Pressure in a Case of Choroidal Osteoma

Abstract: This case report highlights a unique presentation of a dark without pressure lesion in a patient with a choroidal osteoma. The appearance of this patient's fundus suggests a relationship between the change in the photoreceptor structure of dark without pressure and adjacent space-occupying lesions such as tumors or other ocular pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The existence of DWOP lesions has been reported in several diseases, but the incidence rate of DWOP lesions has rarely been reported [ 22 , 23 , 24 ]. In the case series reported by Fawzi A et al [ 7 ] DWOP was found in a 25-year-old girl with myopia and showed no significant progress at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of DWOP lesions has been reported in several diseases, but the incidence rate of DWOP lesions has rarely been reported [ 22 , 23 , 24 ]. In the case series reported by Fawzi A et al [ 7 ] DWOP was found in a 25-year-old girl with myopia and showed no significant progress at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Amani A. Fawzi [ 7 ], WWOP was shown to have no relation to vitreal-retinal traction, but was related to the reflectivity changes in the photoreceptor layer, which is consistent with our research (shown in Figure 1 ). Previous studies have shown that DWOP can be seen in many fundus diseases, including hemoglobinopathy [ 15 ], retinal astrocytoma [ 7 ], white dot syndrome [ 7 ], HLA-B27 anterior middle uveitis [ 7 ], congenital retinal pigment epithelial hypertrophy [ 7 , 22 ], AIDS [ 19 ], Ebola [ 23 ], and choroidal osteoma [ 24 ]. The common feature of DWOP in OCT images is that the EZ is faded or has disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, cases of perilesional DWP enable an insight into their underlying aetiology, where the cause is known. While perilesional areas of DWP have been reported adjacent to non-infectious lesions such as congenital hypertrophy of the retinal pigment epithelium 15 , and choroidal osteomas 16 , they have also been associated with infectious aetiologies such as Ebola retinal lesions. 8 Over a 12-month observational period, following Ebola virus disease (EVD) infection, areas of DWP were observed to retract back towards EVD lesions in some cases, while in other examples were observed to both simultaneously expand and contract at opposing DWP margins suggesting the presence of an unknown prolonged intraretinal stimulus post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…8 The etiology is unclear, but it was suggested to represent a congenital, benign, and incidental lesion that requires no further evaluations. [8][9][10][11][12][13] Two cohort studies on Ebola virus survivors reported dark without pressure lesions in some patients, which may be related to viral disease. 14,15 Herein, we report multimodal imaging ndings in pediatric retinal vasculitis patients who demonstrated DWP.…”
Section: Introductionmentioning
confidence: 99%